PARCHMENT PRESENCE AND TREATMENT WITH VITAMINS ON THE EMERGENCE OF COFFEE SEEDLINGS - Campos, Luiz Fernandes Cardoso; Vendruscolo, Eduardo Pradi; Nascimento, Lucas Marquezan; Campos, Camila Meira de Abreu; Pires, Larissa Leandro; Seleguini, Alexsander (REVISTA DE AGRICULTURA NEOTROPICAL, 2019)
The seedling production of is a stage of great importance for several crops. The seeds of the coffee tree present germination difficulties due to the physical barrier imposed by the parchment. The objective of this study was to evaluate the effect of parchment presence and pre-sowing treatment with vitamins on the emergence of coffee seedlings. The experimental design was completely randomized, in a 2x4 factorial design (parchment presence x types of vitamins), in four replicates with 15 seeds per plot. Vitamins concentration was 100 mg l-1 of thiamine, 100 mg l-1 niacin, 50 mg l-1 thiamine + 50 mg l-1 niacin and a control treatment. The evaluations were performed weekly, with the emerged seedlings being counted until the 76th day after sowing. The emergence percentage was obtained after the 146th day after sowing, counting the number of normal seedlings obtained. The parchment removal increases the speed and the emergence percentage of the coffee seedlings. The treatment with vitamin did not influenced the emergence characteristics of the coffee tree.